Liturgie vom Frühen Mittelalter zum Zeitalter der Konfessionalisierung: Studien zur Geschichte des Gottesdienstes - Odenthal, Andreas (Spätmittelalter, Humanismus, Reformation, 2011)
"Religious rituals mirror human faith and the interpretation of life. In this collection of essays, Andreas Odenthal not only discusses Christian worship in medieval times and in the age of confessionalization, he also places it in the context of social processes and the history of piety. The first section of essays deals with the large variety of medieval liturgy ranging from Mass to the Easter drama, focusing on the Roman form of the liturgy, a part of the Carolingian reform program whose goal was an alliance between the Holy Roman Empire and the papacy. In the second section, the author deals with the Liturgy of the Hours in the Reformation churches. The debate at that time had an impact on the liturgy as well, since it raised the question of which medieval traditions should be preserved and which innovations were due to more recent theological developments. The author shows how the research on the history of the liturgy is relevant for understanding historical processes"--Publisher's website